O tema da morte no itinerário filosófico de Martin Heidegger: do ser para a morte aos mortais que são os homens - Abdala, Amir (2015)
The thesis deals with the death theme in Martin Heidegger s philosophical thought, examining it in the different phases that constitute Heidegger s philosophical itinerary. At Being and time (Sein und Zeit), study published in 1927 and with which this philosofer inscribes his name among the classics of the contemporary thought, the notion of being toward death (Sein zum Tode) is delineated in the center of its existential analysis, projeced from the concern in investigating the meaning of the being. In Heidegger s writings prior to the mid thirty decade, belonging to the titled turning (Kehre), the existential analysis is replaced by the speculations about the history of the being in its veiling e unveiling. In the turning texts, the human being is thought in its correspondence to the destinations of the being, and the death is considered under a new philosophical point of view, revealing itself, under this prism, the mortals who are the men (die Sterblichen sind die Menschen). In concise terms, therefore, it can be claimed that the research renders problematic the relations between being toward death and the mortals who are the men, properly contextualized in the guidelines of Heidegger s thought. In this perspective, it is achieved through an investigative and expository plan whose starting point, expressed in its first chapter, is the reflection about the Dasein as being toward death, trying to understand it in the range of the fundamental ontology. The second chapter intends to identify the tendencies of Heidegger s philosophy under the influx of the turning, featuring its interpretation metaphysics history as forgetfulness of the being and its explicit pretension of transcending the metaphysics, with the restitution of the human essence in its belonging to the being. The third chapter starts from Heidegger s declaration that the essence of the modern technic expresses the conclusion of the metaphysics as a complete hiding of the being, to identify the condition of the human being in the interior of this process and confront it with the notion of being toward death. Chapter four talks about Heidegger s conception of the human essence in its correspondence to the reciprocity originated between being and nothing, the abyss to which belong the mortals who are the men. Lastly, prior to the work s conclusion, the fifth chapter makes the direct comparison between being toward death and the mortals who are the men, with the intention of demarcating their distinctions and articulations